Einflussfaktoren auf den stationären Verlauf von Patienten mit hüftgelenknahen Femurfrakturen: Komplikationen, Liegezeit und Krankenhaussterblichkeit = Factors influencing course of hospitalization in patients with hip fractures - Muhm, Markus Joachim; Weiß, Christel; Winkler, Hartmut (Zeitschrift für Gerontologie und Geriatrie, 2014)
Background: Time of surgery, age, sex, and co-morbidities influence the complication and mortality rate in patients with hip fractures. Patients with relevant co-morbidities, who were hospitalized at the weekend have a higher mortality rate. Complications prolong length of stay (LOS), which results in higher costs and shortage of bed capacity. Objectives: The influence of various factors on hospitalization with emphasis on complications, LOS, and clinical mortality should be observed. Materials and Methods: Retrospectively, 242 patients with hip fractures (>64a) were observed. In addition to age and sex, time of hospitalization and surgery, intensive care therapy, hospital mortality, LOS, comorbidities, ASA, and complications were recorded. Times were assigned to the work week or the weekend or regular or on-call duty service. Results: 29.8 % were hospitalized at the weekend, 66.1% on on-call duty, 24.1% were operated on the weekend, 67.4% on on-call duty. 86.3% were operated <48h after admission. The mortality rate was 8.3%. Longer time to surgery results in more frequent intensive care therapy, prolongs the LOS, and increases overall complications. Advanced age increases mortality and LOS. A higher value of the ASA classification leads to increased mortality; co-morbidities lead to more frequent intensive care therapy. Surgical complications prolong LOS of 10.8d (86.4%). Conclusion: Hospitalization is influenced by age, ASA and co-morbidities as well as by time to surgery and operation in day or late and nighttime service. Early surgery and prevention of surgical complications reduce LOS.